ANALISIS PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TIKET KERETA API ARGO LAWU DI STASIUN BALAPAN SOLO - Laila Putri Shalihah; Titin Hargyatni (MANAJEMEN, 2022)
This research is a quantitative research with the object of research is the passenger of PT. KAI Argo Lawu at Solo Racing Station. The sample in this study were 100 people. Data collection techniques through questionnaires. From the results of data processing, There is an influence of Service Quality on the ticket purchase decision of PT. KAI Argo Lawu at Solo Balapan Station, the arena with a significant level of service quality and a promotion effect on the ticket purchase decision of PT. KAI Argo Lawu at Solo Balapan Station. The value of the coefficient of determination is 0.578 or 57.8%. This means that the quality of service and promotion affect the decision to buy tickets PT. KAI Argo Lawu at Solo Balapan Station was 57.8%, while the remaining 42.2% was influenced by other factors not examined.